FACILE SYNTHESIS, CHARACTERIZATION AND DFT CALCULATIONS OF 2-ACETYL PYRIDINE DERIVATIVES - Haroon ur Rashid; Adnan Shahzad; Zarif Gul; Ezzat Khan; Muhammad Naveed Umar; Muhammad Raza Shah; Awal Noor; Sher Wali Khan (Química Nova)
Deprotonation of 2-acetylpyridine was carried out in the presence of NaH as a phase transfer catalyst instead of NaOH to minimize side products formation. The products were then treated with two equivalents of alkyl/aryl halide to synthesize a variety of acetyl pyridine derivatives. The compounds were structurally characterized by 1H- and 13C-NMR spectroscopy in solution state. Structure of compound 2 was also confirmed in solid state by X-ray diffraction. Electronic properties such as Mulliken charges, frontier molecular orbitals (HOMO-LUMO), ionization energy (IE), electron affinity (EA), global hardness (η), Chemical Potential (µ) and Global electrophilicity (ω) of some compounds were investigated by the same theory using B3LYP-6-311G basis set.